A family of the spiral solutions of the nonlinear Klein‐Gordon equation - Gudkov, V. V. (Mathematical Modelling and Analysis, 1998)
A family of the functions, intended for a construction the exact travelling wave solutions of nonlinear partial differential equations, is given. Exact solutions of the Klein‐Gordon equation with a special potential are obtained. The behavior of complex and hypercomplex solutions of the second order is presented.First Published Online: 14 Oct 2010